Democratization in the Arab World Prospects and Lessons from Around the Globe - Miller, Laurel E. (RAND Corporation, 2012)
Daunting challenges lie ahead for Arab countries where revolutions have upended longstanding authoritarian regimes. This monograph aims to help policymakers understand the challenges ahead, form well-founded expectations, shape diplomatic approaches, and take practical steps to foster positive change.